2004
DOI: 10.1590/s0004-282x2004000200030
|View full text |Cite
|
Sign up to set email alerts
|

Primary melanoma of Meckel's cave: case report

Abstract: -We present a case of trigeminal neuralgia with cranial normal magnetic resonance image (MRI) and computed tomography.The pain was not relieved by carbamazepine and microvascular decompression surgery was done.After two months the pain was similar to the condition before surgery. At this time, MRI showed an expansive lesion in Meckel's cave that was treated with radical resection by extra-dural approach. The pathologic examination revealed a primary melanoma. The follow-up after six months did not show abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Bhandari et al attributed the first case of primary solitary intracranial melanoma to Oogle in 1899 [ 7 ]. Melanomas of Meckel’s cave are even rarer [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhandari et al attributed the first case of primary solitary intracranial melanoma to Oogle in 1899 [ 7 ]. Melanomas of Meckel’s cave are even rarer [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary intracranial meningeal melanomas are rare entities, compromising 1% of all melanoma cases and a mere 0.07% of all brain tumors [ 1 ]. Primary malignant meningeal melanoma of the Meckel’s cave is even rarer [ 2 ]. The prognosis of primary malignant meningeal melanoma can be much better if complete resection is achieved as compared to the patients with CNS metastases from melanomas of other sites [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Leptomeningeal melanosis is a normal variant found in 85% of the population, but heterotrophic melanin in the dura is rare. 5 As a result, dural melanomas are rare, and melanomas of the fifth nerve are even rarer. Only two cases of primary malignant melanoma in the Meckel's cave have been reported in the literature so far.…”
Section: Discussionmentioning
confidence: 99%
“…Only two cases of primary malignant melanoma in the Meckel's cave have been reported in the literature so far. 5,6 Falavigna et al reported the case of a 55-year-old male who presented with worsening right-sided facial pain. The melanoma was radically excised and there was no recurrence at 9-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine carcinoma [63] Adenoid cystic carcinoma [5] Malignant melanotic schwannoma [23,61,101] Squamous cell carcinoma [63] Adenocarcinoma [63] Inflammatory Sarcoidosis [19,69] Amyloidoma [22,24,28] IgG4 disease [63] Necrotizing granulomatous inflammation [63] Inflammatory pseudotumor [63] Hematologic malignancies Primary malignant lymphoma [26] Multiple myeloma [32] NK/T lymphoma [63] Diffuse B-cell lymphoma* Plasmacytoma [63] Marginal zone lymphoma [63] Chronic eosinophilic leukemia [63] Lymphoplasmocytic lymphoma [63] Non-Hodgkin lymphoma [63] Cystic Arachnoid cyst [5,21,34,61,64] Epidermoid cyst [17,29] Meningoceles [102] *Illustrative case report presented in this article should, however, be seen as complementary and not competitive [73], since each one of them carries its own risks and advantages. Even though newly described endoscopic approaches appear promising, clinical experiences remain to be reported and an advanced anatomical knowledge of the neurovascular array within and surrounding the skull base is of utmost priority to assure safety during and after procedures.…”
Section: ] Metastaticmentioning
confidence: 99%